Higher metabolic plasticity in temperate compared to tropical lizards suggests increased resilience to climate change. Issue 2 (17th April 2022) - Sun, Baojun; Williams, Caroline M.; Li, Teng; Speakman, John R.; Jin, Zengguang; Lu, Hongliang; Luo, Laigao; Du, Weiguo
Abstract: Patterns in functional diversity of organisms at large spatial scales can provide insight into possible responses to future climate change, but it remains a challenge to link large‐scale patterns at the population or species level to their underlying physiological mechanisms at the individual level. The climate variability hypothesis predicts that temperate ectotherms will be less vulnerable to climate warming compared with tropical ectotherms, due to their superior acclimatization capacity. However, metabolic acclimatization occurs over multiple levels, from the enzyme and cellular level, through organ systems, to whole‐organism metabolic rate (from this point forwards biological hierarchy). Previous studies have focused on one or a few levels of the biological hierarchy, leaving us without a general understanding of how metabolic acclimatization might differ between tropical and temperate species. Here, we investigated thermal acclimation of three species of Takydromus lizards distributed along a broad latitudinal gradient in China, by studying metabolic modifications at the level of the whole organism, organ, mitochondria, metabolome, and proteome. As predicted by the climate variability hypothesis, the two temperate species T. septentrionalis and T. wolteri had an enhanced acclimation response at the whole organism level compared with the tropical species T. sexlineatus, as measured by respiratory gas exchange rates. However, the mechanisms by which whole organism performance was modified was strikingly different in the two temperate species: widespread T. septentrionalis modified organ sizes, whereas the narrowly distributed T. wolteri relied on mitochondrial, proteomic and metabolomic regulation. We suggest that these two mechanisms of thermal acclimatization may represent general strategies used by ectotherms, with distinct ecological costs and benefits. Lacking either of these mechanisms of thermal acclimatization capacity, the tropical species is likely to have increased vulnerability to climate change.